Operability and Flexibility of Pinch Applications on Heat Exchanger Network in Chemical Industry - Mandalagiri, Levina; Irawan, Anton; Yani, Setyawati (Journal of Chemical Process Engineering, 2021)
The successful energy-saving efforts made by industries impact on not only lowering production costs but also indirectly preserving natural resources as well as reducing the pollution of CO2 which is one of the gases contributing to global warming. Pinch analysis has been widely known for process integration, especially in heat integration, in order to gain energy efficiency and cost efficiency in many industries for decade. The analysis allows selection of efficient heat exchanger network with minimum hot and cold energy requirement. By using pinch analysis, the number of heat exchanger units required could also be minimized which leads to the optimum cost of operational and investment. Pinch analysis is also allowing for the investigation of any pinch problems, such as pinch threshold problems, cross pinch problems, and problems related to incorrect placement of utilities which impacted to the wastefulness of energy consumption. Despite many success studies of highly potential saving of heat integration through pinch analysis, the real implementation of efficient and effective heat exchanger network (HEN) based on pinch analysis is still facing difficulties, for example in term of flexibility and controllability of operation. This paper provides preliminary information in increasing energy efficiency or energy savings when utilizing pinch technology considering operability and flexibility of its operation for retrofitting units for chemical industrial plants.